Patterns of Dysphemism of COVID-19 News in Indonesian Mass Media: Critical Eco-Discourse Analysis - Khotimah, Khusnul; Laksono, Kisyani; Suhartono, Suhartono (International Journal of Innovative Research and Scientific Studies, 2022)
The COVID-19 pandemic has led to the use of specialized terminology that is either new or beyond the lexical limits of its general usage. The mass media use various language tools to package constructive and destructive ideologies related to the environment, such as euphemisms and dysphemisms. This study discusses the patterns of dysphemism and the effect of using dysphemism in reporting on COVID-19 by the Indonesian mass media. This qualitative descriptive study utilized data collected from several Indonesian online media. Distributional and equivalent techniques were used for data analysis. The results showed that the Indonesian mass media applied four types of dysphemism expression units to report COVID-19, i.e., words, phrases, clauses, and sentences. These dysphemisms generally refer to humans, plants, animals, soil, toxic materials, trash and waste, pollution, destruction of nature, and taboos. In addition, the feelings contained in dysphemism are creepy, awful, disgusting, reinforcing, and disrespectful. There are several reasons for using dysphemism, namely: (a) attracting the reader’s attention, (b) confirming speech or strengthening meaning, (c) word variations, (d) provocation, and (e) saving space. Some of the impacts of using dysphemism in society are rude language patterns, irritability, disturbed psychology, and blurred understanding.